Magical mushrooms, mischievous molds - Hudler, George W. (Princeton University Press, 1998)
In this book, George Hudler leads us on a tour of an often-overlooked group of organisms, which differ radically from both animals and plants. Along the way the author stops to ponder the marvels of nature and the impact of mere microbes on the evolution of civilization. Nature's ultimate recyclers not only save us from drowning in a sea of organic waste, but also provide us with food, drink, and a wide array of valuable medicines and industrial chemicals.